Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2011
DOI: 10.1029/2011gl049630
|View full text |Cite
|
Sign up to set email alerts
|

Testing for flow in the north polar layered deposits of Mars using radar stratigraphy and a simple 3D ice-flow model

Abstract: The water‐ice‐rich north polar layered deposits (NPLD) of Mars play a key role in the Martian climate through an active exchange of water vapor with the atmosphere. Conditions are not currently amenable for flow of the NPLD; however, gross morphological evidence for past flow suggests the possibility of a warmer climate in the past. Here we present the first comparison of internal stratigraphy predicted by a flow model with that observed by an orbital radar sounder. We have analyzed radar data from Gemina Ling… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
14
0

Year Published

2015
2015
2019
2019

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 24 publications
(14 citation statements)
references
References 36 publications
(59 reference statements)
0
14
0
Order By: Relevance
“…Because of the discrepancies of internal stratigraphy predicted by ice flow models and those observed in both this study and that of Karlsson et al . [], we posit that there was no significant role for ice flow in the evolution of the troughs on the NPLD.…”
Section: Discussionmentioning
confidence: 94%
“…Because of the discrepancies of internal stratigraphy predicted by ice flow models and those observed in both this study and that of Karlsson et al . [], we posit that there was no significant role for ice flow in the evolution of the troughs on the NPLD.…”
Section: Discussionmentioning
confidence: 94%
“…A variety of geological processes and structures can contribute to geothermal heat flow (e.g., Rezvanbehbahani et al, 2017). This effect is not observed to be occurring in the polar layered deposits (Karlsson et al, 2011), nor is it predicted to occur except possibly at some margins (Sori et al, 2016). Models of Martian midlatitude glaciation similarly found that increases in geothermal heat flux were needed to achieve subglacial melting but also required strain heating of the ice due to internal deformation of flowing ice (Butcher et al, 2017).…”
Section: Discussionmentioning
confidence: 99%
“…It has been argued that the morphology of large portions of the NPLD resembles a flowing ice mass (Winebrenner et al, ), and some numerical modeling studies have predicted that viscous flow should be an important process in PLD evolution (Pathare & Paige, ). However, SHARAD data have revealed that the NPLD's internal stratigraphy is not consistent with ice flow, as observed radar reflectors do not exhibit dips toward the surface as predicted by flow models (Karlsson et al, ). A proposed solution to this inconsistency is that dust‐rich layers in both PLDs effectively break up the large ice mass into smaller portions, preventing interior viscous deformation of the stratigraphy (Smith, ).…”
Section: Discussionmentioning
confidence: 93%